Yeast FKBP-13 is a membrane-associated FK506-binding protein encoded by the nonessential gene FKB2. - Nielsen, J B (1992)
The immunosuppressants FK506 and rapamycin prevent T-cell activation and also inhibit the growth of certain strains of the yeast Saccharomyces cerevisiae. It has previously been shown that yeast contains a 12-kDa cytosolic FK506-binding protein (yFKBP-12), which also possesses peptidylprolyl cis-trans isomerase activity, and that fkb1 strains lacking yFKBP-12 are resistant to rapamycin and sensitive to FK506. The absence of yFKBP-12 permitted the detection and isolation of a second FK506- and rapamycin-binding protein, which is about 13 kDa in size (yFKBP-13) and membrane-associated. Purified yFKBP-13 binds FK506 with 15-fold lower affinity than yFKBP-12 and has peptidylprolyl cis-trans isomerase activity with a similar substrate profile. The sequence of the first 37 N-terminal amino acids was determined, and the yFKBP-13 gene (FKB2) was cloned and sequenced. A hydrophobic putative signal sequence precedes the N terminus of the mature protein. yFKBP-13 most closely resembles the membrane-associated human FKBP-13, which also possesses a signal peptide, whereas yFKBP-12 most closely resembles human FKBP-12. fkb2 and fkb1 fkb2 mutants are viable and unaltered in their sensitivity to FK506, suggesting that yeast possesses an additional target for this drug. Furthermore, fkb2 null mutations confer no change in rapamycin sensitivity. These findings show that yFKBP-13 and yFKBP-12 have distinct functions within the cell.